A Effective Cross Layer Multi-Hop Routing Protocol for Heterogeneous Wireless Sensor Network - Manisha R. Dhage; Srikanth Vemuru (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
In today’s scenario to solve the real world problem heterogeneous wireless sensor is necessary. It consists of different sensor with different sensing capability and different energy level. Routing is important task in HWSN from energy dissipation point of view. In HWSN many routing protocols were proposed but many protocols are for single hop communication between cluster head and sink. Here we have designed multi-hop routing protocol for HWSN, which will be energy efficient and also solve the problem of hot spot using unequal clustering. To make this protocol more energy efficient cross layer information exchange approach is used. Using cross layer communication this protocol will get residual energy, quality of link and neighboring nodes information and this information is used in cluster head selection. Moreover there is no need to do broadcast of residual energy for every round because of RDA (regular data acquisition) nodes. We can predict the energy consumption of node, which will conserve the energy using Energy Efficient Fuzzy Based Cross Layer Protocol (EEFCLP). This proposed protocol can achieve longer sensor lifetime and more energy efficiency.